Coordinated Reset Vibrotactile Stimulation Induces Sustained Cumulative Benefits in Parkinson’s Disease - Pfeifer, Kristina J.; Kromer, Justus A.; Cook, Alexander J.; Hornbeck, Traci; Lim, Erika A.; Mortimer, Bruce J. P.; Fogarty, Adam S.; Han, Summer S.; Dhall, Rohit; Halpern, Casey H.; Tass, Peter A. (Frontiers in Physiology, 2021)
Background: Abnormal synchronization of neuronal activity in dopaminergic circuits is related to motor impairment in Parkinson’s disease (PD). Vibrotactile Coordinated Reset fingertip stimulation (vCR) aims to counteract excessive synchronization and induce sustained unlearning of pathologic synaptic connectivity and neuronal synchrony. Based on a computational study, in two clinical studies we examine the effect of regular (i.e. non-noisy) and noisy vCR stimulation on PD motor symptoms and cortical power changes specifically in the beta band over the sensorimotor cortex. Methods: Computationally, in a network of leaky integrate-and-fire (LIF) neurons with spike-timing-dependent plasticity we study the differences between regular and noisy vCR by using a stimulus model that reproduces experimentally observed central neuronal phase-locking. Study 1 examines 6 PD patients receiving noisy vCR stimulation and their cortical beta power changes over 3 months of noisy vCR. Motor evaluations and at rest electroencephalography (EEG) recordings were assessed off medication pre and post noisy vCR. Study 2 follows 3 patients for 6+ months, 2 of which received regular vCR and one patient from study 1 who received noisy vCR. Motor evaluations were taken at baseline and follow up visits were done approximately every 3 months. In both studies, the Movement Disorders Society-Unified Parkinson’s Rating Scale III (MDS-UPDRS III) was used as the main outcome variable. Results: Computationally, vCR and noisy vCR cause comparable parameter-robust long-lasting synaptic decoupling and neuronal desynchronization. Clinically, both types of stimulation in either study significantly decreased MDS-UPDRS III scores. Additionally, in study 1, a significant decrease in cortical sensorimotor high beta power (21-30 Hz) at rest was shown after 3 months of noisy vCR. Conclusions: In this study of 8 PD patients, regular vCR and noisy vCR were well-tolerated, produced no side effects, and delivered sustained cumulative improvement of motor performance. Reduction of high beta band power over the sensorimotor cortex may suggest noisy vCR is effectively modulating the beta band at the cortical level, which may play a role in improved motor ability. These encouraging therapeutic results enable us to properly plan a proof-of-concept study.